Correction: Safety and efficacy of a freeze-dried trivalent antivenom for snakebites in the Brazilian Amazon: An open randomized controlled phase IIb clinical trial - Mendonça-da-Silva, Iran; Tavares, Antônio Magela; Sachett, Jacqueline; Sardinha, José Felipe; Zaparolli, Lilian; Santos, Maria Fátima Gomes; Lacerda, Marcus; Monteiro, Wuelton Marcelo (PLOS Neglected Tropical Diseases, 2021)
null